Characteristics of Polarographic Catalytic Waves Observed with Bovine-Serum Albumin: Effects of Type of Buffers, pH, Ionic Strength, Calcium, and Tetraalkyl Salts - Kolthoff, I. M. (1974)
Brdička currents observed with bovineserum albumin in ammoniacal buffers with Co(III) and Co(II) as catalysts are identical only when the concentrations of ammonia and ammonium chloride are at least 0.5 M and 0.05 M, respectively. When these conditions are not fulfilled, and in all Tris and borate buffers, the pattern of Brdička currents with Co(III) are quite different from those with Co(II). In such buffers the Co(II) is rapidly reduced at potentials slightly more negative than that at which the Brdička current attains a peak value. In several such buffers the Brdička current may then reduced to zero. In buffers of low ionic strength (about 0.02) and with Co(III), small concentrations of alkali salts greatly increase Brdička currents. When the ionic strength of the buffer is 0.05 M or greater, the effect of alkali salts (up to 0.2 M) is small, but even traces of calcium have a large effect in all buffers with Co(III) as catalyst. Evidence is presented that in the presence of calcium all 17 disulfide groups in bovine-serum albumin are reduced at the dropping mercury electrode. Traces of tetraalkyl salts greatly increase Brdička currents, but the effects is quite different from that of calcium.